ANALISIS FAKTOR YANG MEMPENGARUHI SAFETY PERFORMANCE DENGAN METODE STRUCTURAL EQUATION MODELLING (SEM) (STUDI KASUS PT. COCA-COLA BOTTLING INDONESIA- CENTRAL JAVA) - Febrina Amalia; Darminto Pujotomo; Susatyo Nugroho W (Industrial Engineering Online Journal, 2012)
ABSTRAK PT.Coca-Cola Bottling Indonesia (CCBI)-Central Java has established the safety and health policy in the Company. The safety performance of PT.CCBI-Central Java was good-rated. That achievement strongly depends on all of the efforts made by all parties in the company i.e. corporate leader, the management, and the labor and the reactive and dependent characteristics of safety. Up until now, PT.CCBI-Central Java never knew how strong the factors affecting the achievement of safety performance results in PT.CCBI-Central Java. Based on research conducted by Wu et al (2008), the safety performance is affected by safety leadership and safety climate. Based on these explanations, this research analyzes the effect of safety leadership and safety climate towards safety performance in PT.CCBI-Central Java. The conceptual model used in this study based on the research model of Wu et al (2008). Data measurement is performed by survey using questionnaire distributed to 200 operator level workers of PT.CCBI-Central Java. The Structural Equation Model (SEM) is applied in this study as the data processing method using AMOS 20.0 software. The results of empirical model of safety performance in PT.CCBI-Central Java show that safety leadership has positive and significant impact on safety climate and safety performance at the 5% significance level. Safety climate has positive and significant impact on safety performance at significance level of 5% and mediates the relationship between safety leadership and safety performance. These results can be recommended as evaluation subject for the management of PT.CCBI-Central Java to improve the safety performance in the company.